2017
DOI: 10.1371/journal.pone.0172112
|View full text |Cite
|
Sign up to set email alerts
|

Body size and lower limb posture during walking in humans

Abstract: We test whether locomotor posture is associated with body mass and lower limb length in humans and explore how body size and posture affect net joint moments during walking. We acquired gait data for 24 females and 25 males using a three-dimensional motion capture system and pressure-measuring insoles. We employed the general linear model and commonality analysis to assess the independent effect of body mass and lower limb length on flexion angles at the hip, knee, and ankle while controlling for sex and veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 99 publications
(125 reference statements)
2
12
0
Order By: Relevance
“…This shoe lift may have altered his foot-ankle dynamics 41 , and may be considered in future studies. Many factors such as training time with the powered prosthesis, balance confidence 42 , proprioception, socket fit, muscle strength, body mass/size, posture 43 , and trust in powered devices can have considerable effects on their performance and utilization. Thus, we encourage subject-specific analyses to further investigate potential physical and functional factors of compensatory gait strategies in clinical populations such as transfemoral amputees.…”
Section: Discussionmentioning
confidence: 99%
“…This shoe lift may have altered his foot-ankle dynamics 41 , and may be considered in future studies. Many factors such as training time with the powered prosthesis, balance confidence 42 , proprioception, socket fit, muscle strength, body mass/size, posture 43 , and trust in powered devices can have considerable effects on their performance and utilization. Thus, we encourage subject-specific analyses to further investigate potential physical and functional factors of compensatory gait strategies in clinical populations such as transfemoral amputees.…”
Section: Discussionmentioning
confidence: 99%
“…For one, there is no clear cut-off value to classify pathological gait since all measured parameters vary for each individual. For example, they strongly depend on the patient's height, age, gender, and fitness level [18][19][20]. In addition, many of the measures are insensitive to subtle changes in gait pattern [21].…”
Section: Introductionmentioning
confidence: 99%
“…Greater body mass requires greater production of force by muscles (Kram & Taylor, 1990) and affects net joint movements associated with locomotion in humans (Hora et al, 2017). Reynolds & Hooton (1936) suggested that pelvic structure might respond to body posture and weight; however, as they wrote, their findings were suggestive only, due to methodological errors such as small sample size, incomplete data and problems with interpretations of drawings of the pelvis.…”
Section: Introductionmentioning
confidence: 99%